The Attraction of Martapura Intan Market As A Tourist Object in Banjar District - Muhammad Yasir; Ersis Warmansyah Abbas; Mutiani Mutiani; Sovia Husni Rahmia; Fatwa Nur'aini (Universitas Lambung Mangkurat, 2024)
Martapura Intan Market is a famous gem trading and polishing place in South Kalimantan. Intan Martapura Market, which used to be busy with visitors, is now starting to decrease because buyers' interest is decreasing and promotion and marketing strategies are not yet effective. In fact, Intan Market has aspects in the form of a tourist attraction, which if developed could make Martapura Intan Market a more popular tourist attraction in Banjar Regency. The aim of writing this article is to describe the attractiveness of Martapura Intan Market as a tourist attraction in Banjar Regency. This research uses a qualitative research approach with descriptive research type. Data collection techniques were carried out by conducting observations, interviews, documentation and literature studies. Data analysis uses data reduction techniques, data presentation and drawing conclusions. The results of this research describe that the attraction of Martapura Intan Market as a tourist attraction is in the aspects of cultural tourism and shopping tourism. Cultural tourism related to stone crafts which are processed into various forms and other shopping tourism related to traditional shopping centers that sell various kinds of gemstones and other products from Banjar Regency. Tourist attraction in the aspects of cultural tourism and shopping tourism is something that has an impact. If managed and developed well, Martapura Intan Market will become one of the popular tourist attractions in Banjar Regency.